Onesimus Our Brother : Reading Religion, Race, and Culture in Philemon - Williams, Demetrius K.; Noel, James A., 1948-; Johnson, Matthew V., 1961- (Book collections on Project MUSE., 2012)
"Noel and Johnson make the point that Philemon is as important a letter from an African-American perspective as Romans or Galatians have proven to be in Eurocentric interpretation. Here they gather critical essays by a constellation of African-American scholars, highlighting the latest in interpretive methods and troubling scholarly waters, interacting with the legacies of Hegel, Freud, Habermas, Ricoeur, and James C. Scott as well as the historical experience of African American communities. Onesimus Our Brother opens surprising new vistas on Paul's shortest and, in some ways, most troubling letter."--